The Effectiveness of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) and NSAID-Analgesic Combinations in Optimizing Postoperative Pain Management: A Review - Elsyifa Salsabila; Mally Ghinan Sholih; Diyanah Fauziah Tamimah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Postoperative pain is a common clinical problem resulting from tissue trauma and inflammatory responses, which can hinder patient recovery. One of the most widely used pharmacological therapies is Non-Steroidal Anti-Inflammatory Drugs (NSAIDs), either as monotherapy or in combination with other analgesics. This study aims to evaluate the effectiveness of NSAIDs, both as single agents and in combination therapy, in reducing postoperative pain. The study employed a Systematic Literature Review (SLR) method, with literature searches conducted in the PubMed and Google Scholar databases. A total of 588 articles were identified, of which 20 studies met the inclusion criteria and were analyzed using a narrative synthesis approach based on pain intensity parameters, including the Visual Analog Scale (VAS) and Numeric Rating Scale (NRS). The results indicate that NSAIDs such as ketorolac, ketoprofen, ibuprofen, diclofenac sodium, and dexketoprofen trometamol effectively reduced postoperative pain intensity, with several studies reporting a decrease in VAS scores from moderate pain levels (VAS >4) to mild pain levels (VAS <2) within 24 hours postoperatively. Furthermore, combination therapy of NSAIDs with paracetamol or tramadol demonstrated superior analgesic efficacy, longer pain-free duration, and reduced opioid requirements compared to NSAID monotherapy, without a significant increase in adverse effects. NSAIDs are effective in postoperative pain management. Combination therapy with other analgesics such as paracetamol or tramadol provides more optimal outcomes compared to monotherapy. However, the selection of analgesic agents, dosage, and duration of therapy should be individualized according to the patient’s clinical condition to ensure both safety and therapeutic effectiveness.